Accuracy and precision of two laser dendrometers - Skovsgaard, J.P.; Johannsen, V.K.; Vanclay, J.K. (1998)
Two commercial laser dendrometers were tested under controlled and field conditions, and contrasted with alternative instruments. Testing focused on height Measurement, but also considered distance and remote diameter measurements. Both laser instruments gave very precise estimates, but showed some bias. Users of these and other 'high-tech' instruments are reminded that precision is not synonymous with accuracy. Users should not become complacent about the submillimetre readout, but should calibrate instruments to examine if users' accuracy requirements are satisfied. Instruments may need to be re-calibrated each measurement season and after any mishandling.